Homosexualités et tolérance sociale - Richard, Louis; Seguin, Marie-Thérèse; Groupe de recherche interuniversitaire et interdisciplinaire sur la gestion sociale (Éditions d'Acadie, 1988)
GRIIGES, Groupe de recherche interuniversitaire et interdisciplinaire sur la gestion sociale. Actes d'un colloque tenu du 9 au 11 oct. 1987 à l'Université de Moncton.
Section: 194 pages ; 23 cm
Keywords: 1900-1999; 1980-1989; LGBTQIA2+; amérique du nord; amériques; approches et analyses; canada; cours; discipline; homophobie; hétérosexisme; identités LGBTQIA2+; inégalités; justice sociale; nouveau-brunswick; premier cycle; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

Les lesbiennes et le féminisme - Roy, Carolle (Éditions Saint-Martin, 1985)
Section: 142 pages ; 23 cm
Keywords: 1900-1999; 1970-1979; 1980-1989; LGBTQIA2+; approches et analyses; cours; discipline; europe; france; hétérosexisme; identités LGBTQIA2+; lesbianisme; patriarcat; premiers peuples; périodes historiques; queer; régions géographiques; sexualité; shm4000; systèmes d'oppressions; thématiques

Powers of desire the politics of sexuality - Snitow, Ann Barr; Stansell, Christine; Thompson, Sharon (Monthly Review Press, 1983)
This provocative anthology brings together a diverse group of well-known feminist and gay writers, historians, and activists. They are concerned not only with current sexual issues-abortion, pornography, reproductive and gay rights-but they also raise a host of new issues and questions: How, and in what ways, is sexuality political? Is the struggle for sexual freedom a complement to other struggles for liberation, or will it detract from them? Has the sexual revolution diminished or enriched the lives of women?
Section: 489 p.
Keywords: approches et analyses; cours; discipline; histoire; intersectionnalité; justice sociale; lesbianisme; premier cycle; queer; sciences humaines; sexologie; sexualité; soc2014; thématiques; études féministes